Pearson syndrome masquerading diamond blackfan anemia: a case report - Bartakke, Sandip P.; Sampagar, Abhilasha Ashok; Kamate, Mahesh; Mittal, Nishant (International Journal of Contemporary Pediatrics, 2018)
Pearson syndrome (PS) is rare and often fatal multisystemic mitochondrial disorder. Many of those who survive develop signs and symptoms later in life of a related disorder called Kearns-Sayre syndrome (KSS). 13-month-old male child presented with transfusion dependent anemia since the age of 3 months and was initially labeled as a case of Diamond Black fan Anemia. Mitochondrial and pancreatic enzyme replacement therapy. Through this case report, we attempt to address the fact that possibility of PS, which is often labeled as DBA in initial stages, should be considered in cases of congenital anemia of uncertain etiology. Early diagnosis of PS and interventional therapy in the form of mitochondrial and pancreatic replacement can significantly prolong survival and improve quality of life.